The Brain-Derived Neurotrophic Factor Val66Met Polymorphism Can Protect Against Cognitive Impairment in Multiple Sclerosis - Portaccio, Emilio; Bellinvia, Angelo; Prestipino, Elio; Nacmias, Benedetta; Bagnoli, Silvia; Razzolini, Lorenzo; Pastò, Luisa; Niccolai, Claudia; Goretti, Benedetta; Fonderico, Mattia; Zimatore, Giovanni Bosco; Losignore, Nunzia Alessandra; et al. (Frontiers in Neurology, 2021)
Introduction. Brain Derived Neurotrophic Factor (BDNF) is a member of the neurotrophin family, involved in neuronal survival and synaptic plasticity. The BDNF Val66Met polymorphism is known to reduce BDNF expression and secretion; its role in Multiple Sclerosis (MS) is poorly investigated. Objectives and methods. In this multicenter, retrospective study, we assessed the role of BDNF Val66Met polymorphism on cognitive and motor disability in MS patients consecutively referring to the University of Florence and the Hospital of Barletta. All patients underwent a genetic analysis for the presence of Val66Met polymorphism and a comprehensive neuropsychological examination on the Rao’s Brief Repeatable Battery and the Stroop Color Word Test. Possible predictors of EDSS score and number of failed neuropsychological tests were assessed through liner multivariable regression models. Results. Ninety-eight patients were recruited. Patients with the BDNF Val66Met polymorphism (35.7%) were more frequently males (p = 0.020), more disabled (p = 0.026), and, marginally, older (p = 0.064). In the multivariable analysis, BDNF Val66Met polymorphism was associated with a better cognitive performance (B= - 1.1 ± 0.5, p = 0.027). Higher EDSS score was associated with a progressive disease course (B= 3.4, p <0.001), and marginally with the presence of the BDNF Val66Met polymorphism (B= 0.56, p = 0.066). Discussion. Our results preliminarily suggest a protective role of BDNF Val66Met polymorphism against cognitive impairment in MS patients, possibly related to a detrimental effect of increased BDNF concentration in a neuroinflammatory environment.